Development of a clean hot water drill to access Subglacial Lake CECs, West Antarctica. Issue 85 (25th September 2021) - Makinson, Keith; Anker, Paul G. D.; Garcés, Jonathan; Goodger, David J.; Polfrey, Scott; Rix, Julius; Silva, Alejandro; Smith, Andrew M.; Uribe, José A.; Zamora, Rodrigo
Abstract: Recent drilling successes on Rutford Ice Stream in West Antarctica demonstrate the viability of hot water drilling subglacial access holes to depths >2000 m. Having techniques to access deep subglacial environments reliably paves the way for subglacial lake exploration beneath the thick central West Antarctic Ice Sheet. An ideal candidate lake, overlain by ~2650 m of ice, identified by Centro de Estudios Científicos (CECs), Chile, has led to collaboration with British Antarctic Survey to access Subglacial Lake CECs (SLCECs). To conform with the Scientific Committee on Antarctic Research code of conduct, which provides a guide to responsible scientific exploration and stewardship of these pristine systems, any access drilling must minimise all aspects of contamination and disturbance of the subglacial environment. To meet these challenges, along with thicker ice and 2000 m elevation, pumping and water treatment systems developed for the Subglacial Lake Ellsworth project, together with new diesel generators, additional water heating and longer drill hose, are currently being integrated with the BEAMISH hot water drill. A dedicated test season near SLCECs will commission the new clean hot water drill, with testing and validation of all clean operating procedures. A subsequent season will then access SLCECs cleanly.